Projection of Rice and Clean Water Demand in North Penajam Paser Regency as an IKN Supporting Area by 2045 - Nani Wulandari; Yulian Widya Saputra; Aisyah Trees Sandy; Juwari Juwari (JPG (Jurnal Pendidikan Geografi), 2026)
Population growth affects the demand for food (rice) and clean water, especially in North Penajam Paser Regency as the buffer zone of the Indonesian Capital City. Previous studies examined population projections, rice demand, and clean water needs in North Penajam Paser Regency. However, some of these studies focused on analyzing only the regency area. This study provides more detailed data at the subdistrict level and provides population projections with sex ratios per subdistrict in North Penajam Paser Regency. This study aims to analyze population projections, food (rice) needs, and clean water needs and identify natural resource management strategies that support the sustainability of food and clean water supplies in the buffer zone of the Indonesian Capital City in North Penajam Paser Regency in 2045. This study uses a descriptive quantitative method with a literature review approach and secondary data projections with the application of an exponential model. The results show that population growth, food (rice) needs, and clean water needs are projected to increase significantly. The number of male residents in North Penajam Paser Regency is projected at 135.246 and the number of female residents at 128.224. In line with this trend, rice demand is projected to reach 29.898 tons per year, while clean water demand is estimated at 6.731.655,32 m3 per year. Therefore, it is necessary to optimize agricultural land use, increase local farmer productivity, and strengthen clean water management and distribution systems based on environmental impact analysis to ensure food security and water resource sustainability in North Penajam Paser Regency in the future.